Kinetics of shear band formation and propagation in glassy polycarbonate deformed in simple shear - Gopez, Adolfo Jesus R. (Philippine Engineering Journal)
A technique involving surface marking of simple shear test specimens was used to investigate the formation of shear bands in polycarbonate. Plane simple shear testing was done to produce a single shear band in the test specimen. Testing was done at ambient temperature (T = 23 + 1 degree celcius) and at a constant reference shear strain rate (y=3 10-3 s-1). Results showed that the shear band formed at yield and then propagated in two stages : first by elongation and later by widening. On the shear stress vs. shear strain curve, the elongation stage corresponded to a stress drop after yield and the widening stage corresponded to plastic deformation with a low apparent strain hardening rate. Observation with markers showed that upon retesting, a previously deformed specimen no longer formed a shear band at yield. Instead it deformed uniformly and homogeneously. End effects were also explored. The results of this study confirm previously obtained results in the preliminary testing of polycarbonate. Shear band formation and propagation were related to a defect theory of plastic deformation for glassy amorphous polymers. According to this theory, plastic deformation takes place when there are enough elementary defects or when these defects are made to move at the right velocity. Shear band formation was then explained to be the consequence of the difficulty with which elementary defects could be formed.